Nhân một trường hợp nhóm máu Rh âm mắc bệnh Von Willebrand tại Bệnh viện Trung ương Huế - Hoa, Phan Thị Thùy; Tránh, Nguyễn Văn; Sằng, Đồng Sỹ; Túy, Trần Thị Phương; Cương, Ngô Tứ; Hiếu, Võ Thế; Bông, Nguyễn Văn; Mẫn, Võ Thị Minh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.